Dynamics for teacher training in planning structured teaching for integrator project (Revista Contexto & Educação, 2024)
Teacher training plays a fundamental role in training teachers for structured teaching planning in integrative projects. Structured teaching is a pedagogical approach that seeks to organize content clearly and sequentially, promoting meaningful student learning. In the context of the integrative project, teachers are responsible for developing a teaching plan that integrates different disciplines or areas of knowledge, providing a holistic and interdisciplinary vision to students. The general objective of this work is to establish the set of activities to be developed in the integrative project using the 30-60-10 method. The training proposed for the development of the structured teaching plan for the project used the World Café method. Teacher training in structured teaching planning for integrative projects must be continuous and updated, considering changes in the field of education and the demands of contemporary society.
Keywords: Teacher training; Integrator Project; Method 30-60-10; World Cafe